In-core temperature measurement for the PBMR using fibre-bragg gratings - De Villiers, Gerrit Johannes (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.